Structure elucidation and 13c NMR assignment of an 1,2,4-oxadiazole substituted pyrazole - Neidlein, Richard; Kramer, Walter; Li, Sheng (Journal of heterocyclic chemistry, 1998)
The orientation of the substituent groups in an 1,2,4-oxadiazole substituted pyrazole, formed by reaction of a phenylnitrile oxide with an unsymmetrically substituted hydrazine is determined. One-dimensional methods as the selective INEPT and 13C1H nOe experiments are used. Both techniques provide also an unambiguous assignment of the 13C nmr spectrum.